The Effect of Marketing Strategy on Repurchase Intention with Customer Satisfaction as a Mediating Variable (A Study of R4 Automotive Companies) - Suhandi.s; Teofilus Teofilus; Endi Sarwoko (Publikasi Indonesia, 2026)
The automotive industry in Indonesia is one of the strategic sectors contributing significantly to national economic growth, employment generation, and the development of the manufacturing sector. The automotive industry is highly competitive, making customer retention essential for long-term business sustainability. This study examined the effect of marketing strategy on repurchase intention, with customer satisfaction as a mediating variable. The research was based on theories of consumer behavior, relationship marketing, and service quality. Data were collected through an online questionnaire targeting R4 vehicle consumers in Lampung who had previously purchased an R4 vehicle. The research model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings were expected to provide insights into how marketing strategies influence consumers’ repurchase intentions. This research also aimed to support sales strategy development and measure the extent of repurchase intention among R4 consumers. The study was conducted with the intention of applying the findings within the author’s workplace.